The Effect of Age Diversity on Firm Value with Sustainability Reporting Disclosure as Intervening Variable - Lestari, Ita; Rahayu, Frida; Widyarini, Rodyah (PT. EQUATOR SINAR AKADEMIA, 2025)
This study aims to determine the influence of the Age of the Board of Commissioners on Firm Value with Sustainability Reporting Disclosure as an intervening variable in manufacturing companies in the mining sector and chemical base materials listed on the Indonesia Stock Exchange in 2018-2022. The independent variable in this study is the Age of the Board of Commissioners. The dependent variable in this study is Firm Value which is proxied by Tobin's Q. The intervening variable in this study is Sustainability Reporting Disclosure which is proxied by the economy, environment and social. The research sample amounted to 26 companies engaged in the manufacturing sector with the observation year 2018-2022. The data analysis method used path analysis with SPSS 25 software. The results of the study show that the results of the direct influence test show that 1) The age of the Board of Commissioners has no effect and is not significant on the Firm Value 2) The age of the Board of Commissioners has no effect and is not significant on Sustainability Reporting Disclosure 3) Sustainability Reporting Disclosure has an effect and is significant on Firm Value 4) The age of the Board of Commissioners has no effect and is not significant on Firm Value with Sustainability Reporting Disclosure as an intervening.